1992
DOI: 10.1002/ar.1092340212
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of adrenal mitochondria following stimulation with corticotropin releasing hormone

Abstract: The mitochondria of rat adrenals were investigated qualitatively and quantitatively in different functional states of the adrenal cortex. Following stimulation of the animals with corticotropin releasing hormone (CRH), the corticosterone serum levels reached a maximum 1 hour after stimulation with CRH. The amount of inner mitochondrial membrane within the zona fasciculata increased showing a biphasic time course, with a first maximum 2 hours and a second maximum 8 hours after stimulation. In contrast, a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 49 publications
6
28
0
Order By: Relevance
“…The high expression of Mn-SOD mRNA in the zona fasciculata and reticularis, and its low expression in the zona glomerulosa of the rat adrenal cortex are consistent with the morphology of their mitochondria [13,14]. It has been reported that densely arranged vesicular cristae, representing the active state of fasciculate cells in normal rats, were transformed into a scarce tubulo-vesicular form, representing their inactive or hypo-functional state, by hypophysectomy [1,2,5,6,13,14]. However, the expression of Mn-SOD mRNA in the remaining part of the cortex in hypophysectomized rats was still higher than in hepatocytes of normal rats.…”
Section: Discussionsupporting
confidence: 72%
“…The high expression of Mn-SOD mRNA in the zona fasciculata and reticularis, and its low expression in the zona glomerulosa of the rat adrenal cortex are consistent with the morphology of their mitochondria [13,14]. It has been reported that densely arranged vesicular cristae, representing the active state of fasciculate cells in normal rats, were transformed into a scarce tubulo-vesicular form, representing their inactive or hypo-functional state, by hypophysectomy [1,2,5,6,13,14]. However, the expression of Mn-SOD mRNA in the remaining part of the cortex in hypophysectomized rats was still higher than in hepatocytes of normal rats.…”
Section: Discussionsupporting
confidence: 72%
“…The mitochondrial abnormalities in 21-OH-deficient mice resemble those described in humans with CAH, 18 and differ from the increase in mitochondrial vesicular membranes that occurs following ACTH or CRH administration. 19,20 The remarkable improvement of adrenal structure and function after gene therapy contrasts with the lack of change observed by suppressing excessive ACTH secretion by corticosterone replacement for 7 days (not shown). This suggests that the alterations in adrenal …”
Section: Discussionmentioning
confidence: 97%
“…There is a well-established correlation between the production sites for steroidogenesis in adrenocortical cells, as indicated by the number and density of inner mitochondrial membranes and SER, and the biochemical activity of these cells. 27,28 Likewise, the increase in liposomes, the storage organelles for cholesterol, reflect reduced steroid biosynthesis and a hypofunctional adrenocortical state. 29 Consistent with these assumptions, ACTH injections at a dose sufficient to restore thymus weight induced a strong increase in the number of mitochondria and increased density of their internal membranes while the number of liposomes were markedly reduced.…”
Section: Discussionmentioning
confidence: 99%